Efeito da composição iônica da água no desenvolvimento de larvas de Macrobrachium rosenbergii (De Man, 1879) no estágio II - Mallasen, Margarete [UNESP] (1997)
The importance of the ions presence in water Ca2+, K+, HCO3-, Br-, Sr2+, Mn2+, HPO42-, Li+, MoO42-, S2O32-, Al3+, Rb+, Zn2+, Co2+ and Cu2+ on the development of Macrobrachium rosenbergii at the larval stage II was evaluated, in order to obtain information to optimize the ionic composition of the brackish water used to larviculture this species. Artificial sea water was prepared according to the formulation used by the Crustacean Rearing Laboratory of CAUNESP. In this formula, salts are classified in major elements, minor elements and trace elements. In this experiment, a starvation test was applied. It consisted in keeping larvae of M. rosenbergii, at the stage II, in 30 ml beakers containing 15 ml of brackish water (12‰). The beakers were kept at about 30ºC of controlled air temperature. There were five phases conducted sequencially (phases 1 to 5). Brackish water of different ionic composition, in relation to the trace elements Al3+, Rb+, Zn2+, Co2+ and Cu2+, were evaluated on the first two phases. Differents formulas containing the minor elements Br-, Sr2+, Mn2+, HPO42-, Li+, MoO42- and S2O32 were evaluated on phases 3 and 4. And five media with differents ionic composition containing the major elements Ca2+, K+, HCO3-, and the minor element Br-, were evaluated on phase 5. Three beakers were used per treatment, and each was stocked with six larvae, in a complete randomized experimental design. In order to estimate the average life time, the number of larvae that survived the treatment was counted every eight hours. The data were analyzed through ANOVA and the means were compared by the Tukey test. The trace elements Al3+, Rb+, Zn2+, Co2+ and Cu2+ and the minor elements Sr2+, Mn2+, HPO42-, Li+, MoO42- and S2O32 did not allow an increase of the larvae life time at the second larval stage. These ions could, however, become essential to this organism at the other stages, or could show a retardation effect. Sodium thiosulphate must be added